Paravertebral block is a proper alternative anesthesia for outpatient lithotripsy - Hanoura, Samy (Medknow Publications & Media Pvt Ltd, 2013)
CONTEXT: This study evaluated the effectiveness of paravertebral block as an alternative anesthetic technique for extracorporeal shock wave lithotripsy (ESWL) procedure. A total of 50 patients with renal stones, aged 20-60 years, were randomly allocated into two groups; 25 patients in group P; received unilateral paravertebral block from T8 through L1 with injection of 5 mL 0.5% bupivacaine and 25 patients in group L; received local infiltration by bupivacaine 0.25% (2 mg/kg) into the 30 cm(2) area after localizing the stones site, 10 min before the session. A total of 10 mm visual analogue scale (VAS) was used to evaluate pain every 10 min during the session. At the end of the procedure, total doses of rescue analgesia, the number of shockwaves, their power, and the total duration of shockwave treatment were recorded. After completion of the procedure, the patient was assessed for pain and nausea in the postanesthesia care unit (PACU) using the VAS. Patient's satisfaction and time needed to discharge patients to home also were recorded. Time to do the anesthetic technique was significantly higher (P < 0.001) in group-P than group-L, it was 12.7 ± 2.3 min versus 6.9 ± 1.9 min, respectively; intraoperative rescue analgesia by fentanyl was lesser (P < 0.001) in group-P than group-L, 26.7 ± 6.32 mcg versus 78.6 ± 5.41 mcg, respectively, also time interval between ends of the procedure till discharge to home was significantly higher (P < 0.001) in group-P than group-L, it was 99 ± 17 min versus 133 ± 31 min, respectively. VAS was not significant difference between both groups either intraoperative or postoperative in first hour. Patient's satisfaction was significantly higher (P < 0.05) in group-P than group-L, it was 8.8 ± 1.1 versus 6.1 ± 0.6, respectively. Adverse events were lesser, but not significant in group-P than in group-L. Two patients (8%) in group-L and one patient (4%) in the group-P experienced episodes of postoperative nausea and vomiting (PONV). Paravertebral block is an effective alternative anesthesia for outpatient lithotripsy; multiple level paravertebral blocks provide an optimal anesthetic condition, with acceptable adverse events for ESWL. And, providing proper analgesia during the procedure and in first hour after finishing of the procedure, early discharge to home and providing better patient's satisfactions. AIMS: This study evaluated the effectiveness of paravertebral block as an alternative anesthetic technique for ESWL procedure. SETTINGS AND DESIGN: Prospective open label study. SUBJECT AND METHODS: A total of 50 patients with renal stones, aged 20-60 years, were randomly allocated into two groups; 25 patients in group P; received unilateral paravertebral block from T8 through L1 with injection of 5mL 0.5% bupivacaine and 25 patients in group L; received local infiltration by bupivacaine 0.25% (2 mg/kg) into the 30 cm(2) area after localizing the stones site, 10 min before the session. A total of 10 mm VAS was used to evaluate pain every 10 min during the session. At the end of the procedure, total doses of rescue analgesia, the number of shockwaves, their power, and the total duration of shockwave treatment were recorded. After completion of the procedure, the patient was assessed for pain and nausea in the PACU using the VAS. Patient's satisfaction and time needed to discharge patients to home also were recorded. STATISTICAL ANALYSIS: The findings of the two groups were statistically compared using SPSS version 12 (SPSS Inc., Chicago, IL). Data were expressed as mean ± standard deviation, number, and percentage. Nominal nonparametric data were analyzed using Chi-square test. Parametric data were compared using unpaired t-test. Ordinal nonparametric data were analyzed using Mann-Whitney U-test. RESULTS: Time to do the anesthetic technique was significantly higher (P < 0.001) in group-P than group-L, it was 12.7 ± 2.3 min versus 6.9 ± 1.9 min, respectively; intraoperative rescue analgesia by fentanyl was lesser (P < 0.001) in group-P than group-L, 26.7 ± 6.32 mcg versus 78.6 ± 5.41 mcg, respectively, also time interval between ends of the procedure till discharge to home was significantly higher (P < 0.001) in group-P than group-L, it was 99 ± 17 min versus 133 ± 31 min, respectively. VAS was not significant difference between both groups either intraoperative or postoperative in first hour. Patient's satisfaction was significantly higher (P < 0.05) in group-P than group-L, it was 8.8 ± 1.1 versus 6.1 ± 0.6, respectively. Adverse events were lesser, but not significant in group-P than in group-L. Two patients (8%) in group-L and one patient (4%) in the group-P experienced episodes of PONV. CONCLUSIONS: Paravertebral block is an effective alternative anesthesia for outpatient lithotripsy; multiple level paravertebral blocks provide an optimal anesthetic condition, with acceptable adverse events for ESWL. And providing proper analgesia during the procedure and in first hour after finishing of the procedure, early discharge to home and providing better patient's satisfactions.